Characterization of the Boran and Sahiwal breeds of cattle for economic characters - Trail, J.C.M.; Gregory, K.E. (1981)
Results of a study conducted in the Rift Valley Province of Kenya comparing pedigree Boran & Sahiwal cattle in order to assess their potential as beef producing animals. Analyzes records on cows & their calves for reproductive characters such as age at first calving, calving interval & growth & maternal characters such as weaning weight, calf survival, cow mortality & productivity, & adjusted weight of heifers at 660 days.